Inspiracje encykliki "Laudato si'" dla duszpasterstwa - Fiałkowski, Marek (Verbum Vitae, 2017)
The Laudato si'. On Care For Our Common Home encyclical is the first document of such a status in the Catholic Church devoted to the topic of environmental protection. It finds its context within the post-council teaching of the Church concerning the broadly understood ecological issues, which are treated as the sign of the times. Pope Francis not only builds on the heritage of his predecessors, but also shapes the reality through the elements characteristic of this pontificate. The issue of environmental protection, being part of the social teaching of the Church, presents a big challenge for pastoral activity. This article aims at finding an answer to the question about the inspiration drawn by the Church from the Laudato si' encyclical. In order to achieve this goal, four inspirations for pastoral care have been selected and discussed: (1) the theological aspect of the natural environment, which is often neglected in ecological analyses, is fully presented in the light of Revelation; (2) the ecological conversion, which sees the ecological crisis from the moral perspective; (3) the threats of consumerism, which should be treated as an anti-ecological approach, harmful for both people and the natural environment; (4) the respectful approach toward the world, expressed through a respect for both God and the natural environment.